Presentación de Autores - Centro de Estudios Helénicos (FAHCE) (2009)
PRESENTACIÓN DE AUTORES Lucia Athanassaki. Constantino Baikouzis. Alberto Bernabé Pajares. Ewen Bowie. Fernando Brandão dos Santos. Claude Calame. Lía M. Galán. Filomena Hirata. Juan Lorenzo. Marcelo O. Magnasco. Richard Martin. María das Graças de Moraes Augusto. Juan T. Nápoli. María de Lourdes Rojas Álvarez. María Isabel Santa Cruz. María de Fátima Silva. Fábio de Souza Lessa. Héctor Vucetich. Graciela Zecchin de Fasano.